Microbiological and Clinical evaluation of Neem gel and Chlorhexidine gel on dental plaque and gingivitis in 20-30 years old adults: A Randomized Parallel-Armed, Double-blinded Controlled Trial - Gargi Nimbulkar; Vikram Garacha; Vittaldas Shetty; Ketaki Bhor; Kumar Chandan Srivastava; Deepti Shrivastava; Mohammed G Sghaireen (Journal of Pharmacy and Bioallied Sciences, 2020)
Background: The etiological relationship between the plaque and the gingival inflammation has been long established. The long-term use of chemical antiplaque agents may lead to side effects such as teeth staining and alteration of taste. Therefore, natural plant extracts with potential antibacterial and anti-inflammatory activity have been explored, which are equally effective and safe for long-term use. Objective: The aim of this study was to compare and evaluate effect of neem gel and chlorhexidine (CHX) gel on dental plaque, gingivitis, and bacterial count of Streptococcus mutans and Lactobacilli among 20–30-year-old school teachers in a city of western Maharashtra, over 90 days’ usage. Materials and Methods: A double-blind, parallel armed, controlled, randomized clinical study was conducted among 60 school teachers of 20–30 years’ age group for 90 days. The two study groups were as follows: Group A––2.5% neem gel (n = 30) and Group B––0.2% CHX gel (n = 30). The plaque scores were recorded by Plaque Index (Löe H. The gingival index, the plaque index and the retention index systems. J Periodontol 1967;38:610-6) and gingival scores by Gingival Index (Löe H, Silness J. Periodontal disease in pregnancy. Acta Odontol Scand 1963;21:533-51). Streptococcus mutans and Lactobacilli species count by conventional culture method was carried out at baseline, 30th day and 90thday. Considering P value <0.05 as statistically significant, intergroup comparison was performed using unpaired t test. One-way analysis of variance (ANOVA) test was used followed by Tukey’s post hoc test for intragroup comparison. Results: The mean plaque, gingival scores, and microbial count of S. mutans and Lactobacilli showed significant reduction at 30th and 90th day in neem gel group as well as CHX gel group (P < 0.05). None of the parameter showed any significant change at 30th and 90th day (P > 0.05) on intergroup comparison. Conclusion: The neem gel showed significant decrease in dental plaque, gingival inflammation, and microbial counts, which was comparable to CHX gel proving to be a good herbal alternative. No side effects were reported for use of neem gel over considered period of time.